Effect of dental implant micro-thread designs on stress distribution in bone-implant interface - Tan, S. C.; I. Ibrahim; R. Daud; N. S. Kamarrudin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Dental implants have been used in replacing broken or damaged teeth. There are failures after the operation was done due to lack of primary stability. Through improving the design of the dental implant, primary stability can be achieved. The aim of the study is to analyse the stress distribution at bone-implant interface due to different micro-thread designs. Five types of two-dimension micro-thread shapes dental implant embedded in bone cube are modeled in ANSYS APDL R3. The micro-thread shapes are Straight, Square, V-shaped, Buttress and Reverse Buttress. The models are meshed using element Quad 8-node 183. 106.066N of horizontal force and vertical force are applied on each model to find out the stress distribution pattern and peak Von Mises stress. The study found that micro-thread shapes changed the stress distribution on implant and bone. The peak Von Mises stress was located at the first micro-thread. Cortical bone took large portion of stress compared to cancellous bone. Square micro-thread has the best stress distribution pattern.